2003
DOI: 10.1023/b:pham.0000008039.59875.4f
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Prediction of the Bitterness Suppression of Elemental Diets by Various Flavors Using a Taste Sensor

Abstract: Even though this prediction method does not offer perfect simulation of human taste sensations, the artificial taste sensor may be useful for predicting the bitterness intensity of elemental diets containing various flavors in the absence of results from full gustatory sensation tests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
24
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 17 publications
3
24
0
Order By: Relevance
“…Bitterness-Suppressing Effect of L-Orn and L-Arg on Single or Mixed Solutions of BCAAs As reported in previous articles, 10,11) the bitterness of BCAAs is greater than that of other amino acids. Figure 1 shows the bitterness-suppressing effects of L-Orn and L-Arg on single BCAA solutions as evaluated in gustatory sensation tests.…”
Section: Resultssupporting
confidence: 60%
“…Bitterness-Suppressing Effect of L-Orn and L-Arg on Single or Mixed Solutions of BCAAs As reported in previous articles, 10,11) the bitterness of BCAAs is greater than that of other amino acids. Figure 1 shows the bitterness-suppressing effects of L-Orn and L-Arg on single BCAA solutions as evaluated in gustatory sensation tests.…”
Section: Resultssupporting
confidence: 60%
“…2,3) At the cognitive level, the perceived inhibition of bitterness occurs in the central nervous system in the brain via taste-taste interactions. A second approach to reducing bitterness is to prevent bitterness perception peripherally, using techniques such as encapsulation, molecular inclusion of cyclodextrins 4,5) or complexation with ion exchange resin, 6) tannate, 7,8) fatty acids 9) or food proteins.…”
Section: Taste-masking Effect Of Chlorogenic Acid (Cga) On Bitter Drumentioning
confidence: 99%
“…2001;Keast and Breslin 2002;Ogawa et al, 2005). Meanwhile, Sweeteners and volatile compounds can also impact bitter taste cognitively (Miyanaga et al 2003;Mukai et al 2007). Ogawa et al (2005) found that the bitter taste inhibition of quinine by amino acids might be due to the interaction at the taste receptor site as amino acids maycompete with quinine for the taste receptors, thus, closing the gate of the cation channel transportation and inhibiting the perception of bitterness.…”
Section: Fig 2 Rp-hplc Pattern Of Hydrolyzed Product Of Mpc By Trypmentioning
confidence: 99%